Occurrence of toxic benthic dinoflagellates in water column - Mohammad Noor, Normawaty; Than, Aung; Raduan, Nadiha (2011)
Benthic dinoflagellates are one group of phytoplankton that was given grat concern nowadays. This is due to the many of the species described are able to produce toxin that can harm human being seagresses and corals. However, few studies heve reported that the presence of this species in the water column. These reports are not supporte by scientific data but nore of coincidently. Therefore, this study was conducted to investigate whether water column is also a habitat of benthic dinoflagellates. the abundance of benthic dinoflagellates living in the substrates and water column comprises of benthic dinoflagellates, including toxic species. This study will add new knowledge on the distribution of benthic dinoflagellates, especially toxic species and will help the relevant agencies to manage the occurrence of harmful alga bloom (HAB).